Treatment of Pilonidal Sinus Using 1470nm Diode Laser as Minimally Invasive Technique - Ali Fouad Rashid Al-Khazraji (Iraqi Journal of Laser, 2024)
Background: The term pilonidal sinus refers to a condition that exists in the natal cleft above the coccyx. The incidence rate among males is 2.2-4 times that of females. Sacral abscess characterizes the acute phase, while cyst development or continuous sinus drainage may occur during the chronic phase. In this study, a 1470nm diode laser was used for the treatment of 50 cases of the pilonidal sinus as SiLaT Sinus Laser Therapy. Aim of the study: to assess the safety and the effectiveness of the use of 1470nm-diode laser for treatment of pilonidal sinus by internal destruction of the granulation tissues and epithelialized sinus using radially emitting probe and assessment of any possible complications and patients’ satisfaction. Patients, Materials and Methods: This is a prospective study with 50 patients; all patients were operated on, in the private clinic under local anesthesia, using a 1470 nm diode laser for SiLaT (Sinus Laser Therapy) between February 2023 and February 2024, all patients surveyed and reported having one or more of complications listed in questionnaire paper (if any). Results: The surgery was tolerated by all of the patients. According to the sex and Tezel’s classification the patients are divided into five types, type I ten cases all are male, type II seven cases (five are male and two are female), type III 21 cases (20 cases are male and one case is female), type IV five cases all are male, type V seven cases all are male. All cases have no major complication in the early postoperative period, closure of sinus pit(s) have occurred between 9-22 days. (74%) of cases have mild pain, (6%) of cases have no pain on analgesic regimen, (20%) of cases have moderate pain No patient experienced significant primary bleeding, 16% of cases experienced a serous discharge that lasts for few days until it ceases on its own. No patient experienced infection. 78% of cases return to work on next day post-operatively, 16% of cases after 1 day of sick leave, 6%of cases after 2 days of sick leave. 2% of cases have been suffered from P.N.S. abscess. All patients were satisfied with the outcome of the operation. Conclusion: Diode 1470nm laser sinus laser therapy (SiLaT) is a safe and effective procedure associated with a low incidence of postoperative complications, it is an acceptable, and remarkable substitute for traditional surgical treatment techniques and can be regarded as reliable, effective, and easy to use. Sp